Analisis Faktor–Faktor Risiko Kejadian Filariasis - Reyke Uloli, Soeyoko, Sumarni (Berita Kedokteran Masyarakat (BKM), 2008)
Background: According to WHO report 2001 filariasis, commonly  known as elephantiasis is one of communicable disease which still becomes a public health problem in Indonesia, particularly in rural areas. Filariasis disease can cause permanent deformity,  i.e. swollen  legs, arms and genital  regardless of sexes. Further  impact of such a condition  is  that  the sufferers cannot work normally and  depend  their  lives  to others. Filariasis disease brings great  social,  cultural,  economic  and  psychological  impact. Out  of  five  districts  in  the  province  of Gorontalo, District of Bonebolango shows the highest endemic. The report shows that out of 326 people whose blood has been examined, 105 turn out to be positive (mf rate=34.4%). They are concentrated at one sub district, i.e. sub district of Boneraya (survey 2002), exceeding endemic borderline of an area with mf rate <1% which becomes a threat to economic stability of the area. WHO declares the Global Goal of Elimination of Lympathic Filariasis as a Public Health Problem by 2020, and Indonesia makes a follow up by determining filariasis elimination as a priority program  of  communicable  disease  eradication. Environmental,  behavioral  and  social  cultural  factors  are  risk factors which minimize  prevalence of  filariasis.Objective: To identify risk factors related to cases of filarisis at District of Bonebolango, Province of Gorontalo.Method:  The  study was  observational with  case  control  design. Odds Ratio  (OR) was  used  to  find  out  risk factor estimation of filariasis prevalence.  Interview was conducted  to respondents with positive microfilaria and equal control. Total samples were as many as 140 respondents. Data analysis used Chi Square and logistic regression.Result: The result of univariable and bivariable analysis showed that risk factors related to filariasis prevalence were behavioral factors, i.e. use of mosquito net (OR=11, 5), use of ventilation wire screen (OR=2.078), use of long  sleeves  (OR=0,  014),  knowledge  (OR=2,  004)  and  environmental  (OR=2,  215) However,  the  result  of multivariable analysis  showed  that  the  risk  factors were behavioral with  such as use of mosquito net  (OR=9, 568), use of long sleeves (OR=2, 870), knowledge (OR=2, 485) and environmental (OR=3.563)Conclusion: Behavioral  (do  not  used  of mosquito  net  and  do  not  used  long  sleeves), Social  cultural  (low knowledge)  and  environmental  factors were  risk  factors  of  filariasis.Keywords: behavioral, social cultural, environmental,  risk of  filariasis, case control